Application of Compromise Programming in the Energy Generation Planning - Osmani, Fisnik (Array, 2021)
The need for the right electricity planning is closely related to the analysis that has to be done on its generating capacity. Of course, in order to make such planning, the choice of the method by which the process is carried out must be considered. The inclusion of multiple objectives (goals) enables us to create models that are useful in researching and expanding electricity generation systems. Compromised programming used in this paper aims to find compromise solutions among different conflicting objectives in the electricity generation system. One such case is the goal of minimizing the cost and CO2 emissions. Using this logic, the paper deals with an example of electricity generation planning for a given region.